Regulation of Small Mitochondrial DNA Replicative Advantage by Ribonucleotide Reductase in Saccharomyces cerevisiae. Issue 9 (1st September 2017) - Bradshaw, Elliot; Yoshida, Minoru; Ling, Feng
Abstract: Small mitochondrial genomes can behave as selfish elements by displacing wild-type genomes regardless of their detriment to the host organism. In the budding yeast Saccharomyces cerevisiae, small hypersuppressive mtDNA transiently coexist with wild-type in a state of heteroplasmy, wherein the replicative advantage of the small mtDNA outcompetes wild-type and produces offspring without respiratory capacity in >95% of colonies. The cytosolic enzyme ribonucleotide reductase (RNR) catalyzes the rate-limiting step in dNTP synthesis and its inhibition has been correlated with increased petite colony formation, reflecting loss of respiratory function. Here, we used heteroplasmic diploids containing wild-type (rho + ) and suppressive (rho − ) or hypersuppressive (HS rho − ) mitochondrial genomes to explore the effects of RNR activity on mtDNA heteroplasmy in offspring. We found that the proportion of rho + offspring was significantly increased by RNR overexpression or deletion of its inhibitor, SML1, while reducing RNR activity via SML1 overexpression produced the opposite effects. In addition, using Ex Taq and KOD Dash polymerases, we observed a replicative advantage for small over large template DNA in vitro, but only at low dNTP concentrations. These results suggest that dNTP insufficiency contributes to the replicative advantage of small mtDNA over wild-type and cytosolic dNTP synthesis by RNR is an important regulator of heteroplasmy involving small mtDNA molecules in yeast.